2021
DOI: 10.17079/jkgn.2021.23.2.117
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Auricular Acupressure on Sleep in Older Adults with Sleep Disorders

Abstract: The purpose of this study was to determine the effects of auricular acupressure on sleep in older adults with sleep disorders. Methods: This was a randomized, single-blind, sham-controlled study. The Pittsburgh Sleep Quality Index (PSQI) and Fitbit Charge HRTM helped assess subjective sleep quality and objective sleep quantity, respectively. In addition, melatonin levels were measured. The participants aged over 65 years were randomly assigned to the experimental group (n=26) and sham control group (n=25). PSQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 24 publications
3
11
0
Order By: Relevance
“…Degree of sleep was assessed using the Oviedo Sleep Questionnaire [ 43 ] (n = 1) and sleep journals (n = 1). A total of 14 studies reported that non-pharmacological sleep interventions were effective in older adults [ 14 , 15 , 37 , 38 , 39 , 40 , 41 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. One study reported that the effectiveness of the intervention was not confirmed [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Degree of sleep was assessed using the Oviedo Sleep Questionnaire [ 43 ] (n = 1) and sleep journals (n = 1). A total of 14 studies reported that non-pharmacological sleep interventions were effective in older adults [ 14 , 15 , 37 , 38 , 39 , 40 , 41 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. One study reported that the effectiveness of the intervention was not confirmed [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies that applied auricular acupressure presented the mean/SD for deep sleep duration [ 14 , 15 ] and melatonin concentrations [ 15 ] in addition to sleep quality; these measurements were also included in the meta-analysis. We analyzed 13 outcome measures.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations